2003
DOI: 10.1128/aem.69.12.7328-7335.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro andIn Vivo Studies of the Yrp1 Protease from Yersinia ruckeri andIts Role in Protective Immunity against Enteric Red MouthDisease ofSalmonids

Abstract: Yersinia ruckeri, the etiological agent of the enteric red mouth disease (ERM) of salmonids, produces Yrp1, a serralysin metalloprotease involved in pathogenesis. We describe here the hydrolytic and immunogenic properties of Yrp1. The protease was able to hydrolyze different matrix and muscle proteins as laminin, fibrinogen, gelatine, actin, and myosin but not type II and IV collagens. In addition, the Yrp1 protein, when inactivated by heat and used as an immunogen, was able to elicit a strong protection again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…These results are consistent with previous studies in which induction of Pcds promoter required the presence of cysteine in the culture medium (Méndez et al ., ) and high concentrations of iron inhibited Pyhl promoter (Fernández et al ., ). On the contrary, the promoter of yctCBA operon (Pyct) involved in in vivo citrate uptake (Navais et al ., ) and the protease Yrp1 (Pyrp1) (Fernández et al ., ) were the promoters with the highest bioluminescence level on NA (Fig. A).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with previous studies in which induction of Pcds promoter required the presence of cysteine in the culture medium (Méndez et al ., ) and high concentrations of iron inhibited Pyhl promoter (Fernández et al ., ). On the contrary, the promoter of yctCBA operon (Pyct) involved in in vivo citrate uptake (Navais et al ., ) and the protease Yrp1 (Pyrp1) (Fernández et al ., ) were the promoters with the highest bioluminescence level on NA (Fig. A).…”
Section: Resultsmentioning
confidence: 93%
“…B and C). The colonization of these organs was previously described by Fernández and colleagues () who used an inducible β‐galactosidase expression system to monitor bacterial tissue distribution in rainbow trout. This bacterial distribution pattern is also consistent with former studies, in which Avci and Birincioglu () described hyperaemia and haemorrhages in the swim bladder after intraperitoneal injection with Y. ruckeri .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve Y. ruckeri strains (146, 147, 148, 149, 150, 3585, 4319, 1386, 955, 956, A100, and A102) (21,47) were positive for the production of siderophores in CAS-agar plates. In addition, PCR assays for the detection of rucC and rupG confirmed the presence of these genes in all the strains tested, even though three different plasmid profiles, represented by strains 955, 956, and the rest of the strains, respectively, were analyzed.…”
Section: Fig 2 Genetic Organization Of Ivii Iviiimentioning
confidence: 99%
“…Until now, the only molecule whose involvement in virulence has been proved is the protease Yrp1 (20,21), but it is only produced by Azo ϩ strains (47). Previously, Romalde et al (42) showed that the extracellular products of Y. ruckeri, which included lipase, protease, and cytotoxic and hemolytic activities, reproduce some characteristic symptoms of this pathology, such as hemorrhage in the mouth and intestine.…”
mentioning
confidence: 99%